SYSTEM ADMINISTRATION ACCEPTANCE OF NEW STUDENTS IN HIGH SCHOOL SAOTA CHARISMA GENERAL IN JAKARTA WITH EAST DBASE III PLUS - Iin Rohmaniah; Ir. Aqwam Rosadi Kardian. Skom. MM (Jurnal Sistem Informasi, 2000)
In every activity has a system, as well as new students at SMU Sapta Charisma has asystem that is new admissions system. When school was recently founded, a newadmissions system using manualisasi system but in recent years has been replacedwith a new admissions system that uses a computerized system.The advantages of using a computerized system is a computerized system hasaccurate results or outputs with inputs, then using a computerized system is likely tomake errors that occur while recording activity is smaller than the manual system.